2020
DOI: 10.1002/jsc.2313
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the drivers of product innovation in emerging markets: The African perspective

Abstract: African firms have made some significant progress in product innovation through human capital development and firm competitiveness. However, these firms need to continuously focus on talent hunting and development as well as strategic collaborations to reap the full benefit of product innovation. Key Points:1. Human capital development efforts in Africa has made a significant impact on product innovation 2. Firm competitiveness in African markets currently drives product innovation 3. Networking and strategic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Human Resources (Seaden et al, 2003), (Sexton and Barrett, 2004), , (Capitanio et al, 2009), (Zhang et al, 2009), (Dachyar et al, 2013), (Ozorhon et al, 2014), (Xue et al, 2014), , (Ozorhon and Oral, 2016), (Kallmuenzer, 2018), (Divisekera and Nguyen, 2018), (Pikkemaat et al, 2018), (Revilla and Rodríguez-Prado, 2018), (Atiase and Dzansi, 2020); Human Resource Management Practices (Kamath et al, 2009), (Bourke and Crowley, 2015), (Tajeddini and Martin, 2020), (Mousavi et al, 2021); Competent Technical Staff (Nijkamp and Reggiani, 2000), (Chen et al, 2010), (Chaminade and De Fuentes, 2012), (Velev and Veleva, 2019); Motivation (Giardini and Kyllönen, 2004), (Kamath et al, 2009); Teamwork/Coordination (Prajogo and Sohal, 2003), (Fortuin et al, 2007), (Koc and Ceylan, 2007), (Chang and Yeh, 2009), , (Nordli, 2018); Selective Recruitment (Manley and Mcfallan, 2006), (Diaz-Delgado et al, 2019), (Atiase and Dzansi, 2020); Employee participation/Engagement ; Innovation Champions (Nam and Tatum, 1997), (Blayse and Manley, 2004), (Gambatese and Hallowell, 2011b), (Xue et al, 2014); Available Skill Levels (Ilter et al, 2008); Organization Career Management (Zhu and Cheung, 2017); Good Internal Communication Systems…”
Section: Factors Of Hrm Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human Resources (Seaden et al, 2003), (Sexton and Barrett, 2004), , (Capitanio et al, 2009), (Zhang et al, 2009), (Dachyar et al, 2013), (Ozorhon et al, 2014), (Xue et al, 2014), , (Ozorhon and Oral, 2016), (Kallmuenzer, 2018), (Divisekera and Nguyen, 2018), (Pikkemaat et al, 2018), (Revilla and Rodríguez-Prado, 2018), (Atiase and Dzansi, 2020); Human Resource Management Practices (Kamath et al, 2009), (Bourke and Crowley, 2015), (Tajeddini and Martin, 2020), (Mousavi et al, 2021); Competent Technical Staff (Nijkamp and Reggiani, 2000), (Chen et al, 2010), (Chaminade and De Fuentes, 2012), (Velev and Veleva, 2019); Motivation (Giardini and Kyllönen, 2004), (Kamath et al, 2009); Teamwork/Coordination (Prajogo and Sohal, 2003), (Fortuin et al, 2007), (Koc and Ceylan, 2007), (Chang and Yeh, 2009), , (Nordli, 2018); Selective Recruitment (Manley and Mcfallan, 2006), (Diaz-Delgado et al, 2019), (Atiase and Dzansi, 2020); Employee participation/Engagement ; Innovation Champions (Nam and Tatum, 1997), (Blayse and Manley, 2004), (Gambatese and Hallowell, 2011b), (Xue et al, 2014); Available Skill Levels (Ilter et al, 2008); Organization Career Management (Zhu and Cheung, 2017); Good Internal Communication Systems…”
Section: Factors Of Hrm Functionsmentioning
confidence: 99%
“…Factors of External Environment (Seaden et al, 2003), (Bossink, 2004, (Capitanio et al, 2009), (Zhang et al, 2009), (Kask, 2011), , (Xue et al, 2014), (Meng and Brown, 2018), (Quirapas et al, 2018, (Kafetzopoulos and Skalkos, 2019); Environmental Sustainability (Chang and Hughes, 2012), (Ozorhon and Oral, 2016), (Argothy and Álvarez, 2019), (Owolabi et al, 2019); Collaborative Relationship Network (Nijkamp and Reggiani, 2000), (Abdul Hamid and Abd. Rahman, 2014), (Divisekera and Nguyen, 2018), (Pikkemaat et al, 2018), (Kafetzopoulos and Skalkos, 2019), (Atiase and Dzansi, 2020); Social Network (Nijkamp and Reggiani, 2000), ; Partnering/Networking with Specialist Experts (Nijkamp and Reggiani, 2000), (Ilter et al, 2008), (Chen et al, 2010), (Kinkel and Som, 2010), (Liddle and El-Kafafi, 2010), (Kramer et al, 2011), (Narayanan and Parvin Hosseini, 2014); Industry Relationships (Nijkamp and Reggiani, 2000), (Blayse and Manley, 2004); Opportunity (Gambatese and Hallowell, 2011a), (Bhuiyan et al, 2017), (Velev and Veleva, 2019), , (Mousavi et al, 2021); New Technology (Manley and Mcfallan, 2006), (Liddle and El-Kafafi, 2010), (Drnevich et al, 2011),…”
Section: External Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Egbetokun et al (2016) argue that innovation involves the connectivity of several actors in which producers of products depend on their external partners such as suppliers, customers, and competitors for information on new product development. Atiase & Dzansi (2020) found that human capital, collaborative networks, and competitiveness all have a signi cant effect on innovation among rms in the African continent. Studying the Ghanaian situation, (Abdulai, Murphy, & Thomas, 2020) found that University-industry collaboration promotes innovation among rms, while the informal transfer of knowledge from Universities had no signi cant effect.…”
Section: The Main Drivers Of Innovationmentioning
confidence: 99%
“…Second, financing for industry, particularly SMEs, is a major hindrance to effective participation in GVCs. Third, there are inadequate specialized skills at the professional and technical levels to meet global market requirements.Fourth, insufficient R&D, innovation and technology investment limits the degree of participation in and value derived from the value chain(Atiase & Dzansi, 2020;Atiase, Kolade, & Liedong, 2020). Fifth, the cost of doing business can be pretty high in many African countries, which negatively impacts companies' competitiveness.…”
mentioning
confidence: 99%